Augmentation of Antitumor Immunity by Fusions of Ethanol-Treated Tumor Cells and Dendritic Cells Stimulated via Dual TLRs through TGF-β1 Blockade and IL-12p70 Production - Koido, Shigeo (Public Library of Science, 2013)
The therapeutic efficacy of fusion cell (FC)-based cancer vaccine generated with whole tumor cells and dendritic cells (DCs) requires the improved immunogenicity of both cells. Treatment of whole tumor cells with ethanol resulted in blockade of immune-suppressive soluble factors such as transforming growth factor (TGF)-β1, vascular endothelial growth factor, and IL-10 without decreased expression of major histocompatibility complex (MHC) class I and the MUC1 tumor-associated antigen. Moreover, the ethanol-treated tumor cells expressed “eat-me” signals such as calreticulin (CRT) on the cell surface and released immunostimulatory factors such as heat shock protein (HSP)90α and high-mobility group box 1 (HMGB1). A dual stimulation of protein-bound polysaccharides isolated from Coriolus versicolor (TLR2 agonist) and penicillin-inactivated Streptococcus pyogenes (TLR4 agonist) led human monocyte-derived DCs to produce HSP90α and multiple cytokines such as IL-12p70 and IL-10. Interestingly, incorporating ethanol-treated tumor cells and TLRs-stimulated DCs during the fusion process promoted fusion efficiency and up-regulated MHC class II molecules on a per fusion basis. Moreover, fusions of ethanol-treated tumor cells and dual TLRs-stimulated DCs (E-tumor/FCs) inhibited the production of multiple immune-suppressive soluble factors including TGF-β1 and up-regulated the production of IL-12p70 and HSP90α. Most importantly, E-tumor/FCs activated T cells capable of producing high levels of IFN-γ, resulting in augmented MUC1-specific CTL induction. Collectively, our results illustrate the synergy between ethanol-treated whole tumor cells and dual TLRs-stimulated DCs in inducing augmented CTL responses in vitro by FC preparations. The alternative system is simple and may provide a platform for adoptive immunotherapy.